Food supplements to reduce stunting in Pakistan: a process evaluation of community dynamics shaping uptake - Shehla Zaidi; Jai K. Das; Gul Nawaz Khan; Rabia Najmi; Mashal Murad Shah; Sajid B. Soofi (BMC, 2020)
Abstract Background There is an increasing interest in use of food supplements to prevent childhood stunting, however the evidence on the process indicators is scarce. We in this study explore the barriers to the effective implementation of food supplementation programs and the possible mitigation strategies which can guide the design of future programs. Methods We undertook a process evaluation of a stunting prevention food supplementation pilot program in rural Pakistan that distributed Wheat Soy Blend (WSB) to pregnant & lactating women, and Lipid-based Nutrient Supplement (LNS) and micronutrient powder (MNP) to < 5 years children. We used a mixed methods approach through a quantitative survey of 800 households and conducted 18 focused group discussion (FGDs) (with male and female caregivers), 4 FGDs (with Community Health Workers (CHWs)) and 22 key informant interviews (with district stakeholders) to evaluate the community side factors affecting uptake through five parameters: value, acceptability, receipt of supplement, usage and correct dosage. Results The findings show that proportionately few beneficiaries consumed the full dose of supplements, despite reasonable knowledge amongst caregivers. Sharing of supplements with other household member was common, and the full monthly stock was usually not received. Qualitative findings suggest that caregivers did not associate food supplements with stunting prevention. WSB was well accepted as an extra ration, LNS was popular due its chocolaty taste and texture, whereas MNP sprinkles were perceived to be of little value. The cultural food practices led to common sharing, whereas interaction with CHWs was minimal for nutrition counselling. Qualitative findings also indicate CHWs related programmatic constraints of low motivation, multi-tasking, inadequate counselling skills and weak supervision. Conclusion We conclude that the community acceptability of food supplements does not translate into optimal consumption. Hence a greater emphasis is needed on context specific demand creation and focusing on the supply side constraints with improved logistical planning, enhanced motivation and supervision of community workers with involvement of multiple stakeholders. While, similar studies are needed in varying contexts to help frame universal guidelines. Trial registration ClinicalTrials.gov Identifier: NCT02422953 . Registered on April 22, 2015.